PERANAN HOME INDUSTRY GENTENG TERHADAP KEHIDUPAN SOSIAL EKONOMI PENGUSAHA KECIL GENTENG - subiyantoro; Aminudin Azis; Agustinus Doedyk Setiyawan (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2018)
Indonesia's economic strength basically lies on the micro, small and medium sectors (MSME). From the population of business entrepreneurs which reaches the total of 99.9%, this sector is able to absorb employment of 96.7% or 114,819,199 people and reach 60.34% of Indonesia's gross domestic product (GDP). This data shows that the MSME business has a very strategic role in Indonesia economy. Besides being a major player in economic activities in various sectors, MSMEs are also the largest providers of employment, important players in the development of local economic activities and in community empowerment, as creators of new markets and resources, and have an important role in maintaining the balance of payments through Export activities. On a small scale, the roof tile house industry in Gulun Village, Maospati District, Magetan Regency shows no less importance in the socio-economic life of the Gulun Village community. The home industry implications for the social life of the Gulun Village community which include jobs, income, and education level are very significant. The functioning of the roof tile house industry as a village financial institution so far has supported the creation of community welfare in Gulun Village. Besides absorbing a lot of labor, these entrepreneurs are able to send their children to a higher education level, some of them even reach university level.